2021
DOI: 10.3340/jkns.2020.0294
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiological Parameters to Predict Clinical and Radiological Outcomes after Laminoplasty

Abstract: Many studies have focused on pre-operative sagittal alignment parameters which could predict poor clinical or radiological outcomes after laminoplasty. However, the influx of too many new factors causes confusion. This study reviewed sagittal alignment parameters, predictive of clinical or radiological outcomes, in the literature. Preoperative kyphotic alignment was initially proposed as a predictor of clinical outcomes. The clinical significance of the K-line and K-line variants also has been studied. Sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(115 reference statements)
2
2
0
Order By: Relevance
“…23 Preoperative T1S and C2-C7 SVA do not predict changes in cervical curvature after laminoplasty. 24,25 Similarly to the previous studies, we discovered that preoperative T1S and C2-C7 SVA had no significant correlation with postoperative cervical kyphosis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…23 Preoperative T1S and C2-C7 SVA do not predict changes in cervical curvature after laminoplasty. 24,25 Similarly to the previous studies, we discovered that preoperative T1S and C2-C7 SVA had no significant correlation with postoperative cervical kyphosis.…”
Section: Discussionsupporting
confidence: 73%
“…However, some investigators have found no significant correlation between the loss of cervical curvature and preoperative T1S 23 . Preoperative T1S and C2–C7 SVA do not predict changes in cervical curvature after laminoplasty 24,25 . Similarly to the previous studies, we discovered that preoperative T1S and C2–C7 SVA had no significant correlation with postoperative cervical kyphosis.…”
Section: Discussionsupporting
confidence: 71%
“…The relationships between preoperative radiographic parameters and loss of cervical lordosis following laminoplasty have been fairly well studied. Several studies have concluded that a high T1 slope and the difference between T1 slope and C2-C7 lordosis can predict the loss of lordosis following laminoplasty [9][10][11][12][13][14][15][16][17][18]. The relationship between loss of cervical lordosis following laminoplasty and spinal parameters beyond the regional cervical spine on full-length scoliosis X-rays (i.e., pelvic incidence, lumbar lordosis, sagittal vertical axis from C7-S1) have been understudied by comparison.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the pathogenesis of OPLL, on one hand, OPLL demonstrates racial differences in its incidence, which is especially high in East Asian males [ 10 , 11 ]. A previous study in North America showed that the prevalence of OPLL varied among races: 4.8% in Asian Americans, 1.3% in Caucasian Americans, 1.9% in Hispanic Americans, and 3.2% in Native Americans [ 12 ].…”
Section: Introductionmentioning
confidence: 99%